2021
DOI: 10.3390/plants10091755
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional Composition and Health Benefits of Various Botanical Types of Melon (Cucumis melo L.)

Abstract: Characterizing the diverse melon cultivars for nutrition aids in crop improvement and promoting a healthy diet. Here, we used in vitro assays to characterize the nutritional qualities and health-beneficial effects of 30 melon (Cucumis melo L.) genotypes, including 10 improved cultivars, 16 landraces, and 4 wild types collected from different parts of India. Two landraces (Sidoota and Alper Green) had the highest (12.20 and 11.25) total soluble solids (TSS) contents. The Sidoota and Pappusa landraces had high r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
2
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 38 publications
1
21
2
1
Order By: Relevance
“…The TFC and CAC values in the present study were lower than those reported by Benmeziane et al (2018) for melon jam. Manchali et al (2021) revealed that the SSC of melon genotypes ranged from 20 to 61%, which was lower than the current analysis. The TSS and ASC in Indian melon were observed by Pandey et al (2021), which were lower than the findings obtained in this study.…”
Section: Table (4): Means Comparison (Lsd) Of Fruit Morphological Cha...contrasting
confidence: 92%
See 2 more Smart Citations
“…The TFC and CAC values in the present study were lower than those reported by Benmeziane et al (2018) for melon jam. Manchali et al (2021) revealed that the SSC of melon genotypes ranged from 20 to 61%, which was lower than the current analysis. The TSS and ASC in Indian melon were observed by Pandey et al (2021), which were lower than the findings obtained in this study.…”
Section: Table (4): Means Comparison (Lsd) Of Fruit Morphological Cha...contrasting
confidence: 92%
“…Likewise, DPPH activity was increased in samples with higher levels of polyphenols, TTA, and TSS, showing that these are important antioxidants in melons. Melon genotypes assessed for TPC in this study had substantially higher values than values reported in previous studies by Manchali et al (2021) and Pandey et al (2021) that studied several Indian types of melon. The TFC and CAC values in the present study were lower than those reported by Benmeziane et al (2018) for melon jam.…”
Section: Table (4): Means Comparison (Lsd) Of Fruit Morphological Cha...contrasting
confidence: 80%
See 1 more Smart Citation
“…Initially, the pH was 6.28 and 6.05, TA 1.43 and 1.96 g CE/L for the Jimbee and Okashi melon musts, respectively. These values are in the range of other fresh melon cultivars recently reported [ 21 ]. The h° was 65° for the Jimbee and 109° for the Okashi musts, due to its typical orangeness, and pale green-slightly yellow flesh color, respectively.…”
Section: Resultssupporting
confidence: 75%
“…It also contains vitamin C, flavonoids, vitamin B, and fiber and is naturally low in fat and sodium. In addition, it has no cholesterol and provides many essential nutrients, especially potassium (Manchali et al, 2021). Furthermore, melons used as vegetables have flavonoids, alkaloids, and bitter elements, which increase health advantages (Gómez-García et al, 2020).…”
Section: Introductionmentioning
confidence: 99%